Mediterranean Crossings : The Politics of an Interrupted Modernity - Chambers, Iain (Book collections on Project MUSE., 2008)
An interdisciplinary interpretation of the Mediterranean as an extraordinarily fluid, heterogeneous cultural and historical formation, by a leading cultural theorist.